Acute Bronchiolitis To Pediatric Inpatient Clinic In Patients Under 2 Years Old, Installed with Diagnosis Investigation of the Relationship of Bronchiolitis and Asthma - Selin Kuzucu; İpek Türktaş; Tuğba Bedir Demirdağ; Meltem Polat; Hasan Tezer; Anıl Tapısız; Nazmi Mutlu Karakaş; Ayşe Tana Aslan; Hakan Tüzün (Gazi Medical Journal)
Objective: Previously considered a uniform disease, bronchiolitis has been revealed through research as heterogeneous, displaying varied phenotypes and clinical-histopathological differences among patients. Our study aimed to explore distinctions among children hospitalized with acute, severe bronchiolitis and identify potential asthma risk factors. Methods: Between January 2017 and November 2022, we examined hospitalized children under 2 years with moderate to severe acute bronchiolitis. Disease severity was assessed using the bronchiolitis severity score developed by the Turkish Thoracic Society. The asthma risk was evaluated using the modified Asthma Predictive Index (mAPI) designed for predicting future asthma in bronchiolitis cases. Results: A total of 156 patients were studied, with 41% having previous bronchiolitis hospitalizations (multiple hospitalization group) and 59% having first-time hospitalizations (first hospitalization group). Middle rales, wheezing, and tachypnea were more frequent in the multiple hospitalization group, with a 1-unit increase in respiratory rate, increasing readmission risk by 1.048 times. Assessing patients by “API”, 64.1% were “API” (+) and 35.9% were “API” (-). Among “API” (+) patients, 69% were male, compared to 48.3% among “API” (-) patients-a significant difference. Wheezing occurred in 48% of “API” (+) patients and 30.3% of “API” (-) patients - also significant. Conclusion: The majority of bronchiolitis cases were linked to asthma, with a significant 48.7% having a family history. This major risk factor implies a prevalent asthma phenotype. Moreover, 41% of patients with repeated hospitalizations and 64.1% API (+) reinforce this view. In summary, an early identification of patients at risk of asthma is crucial for tailoring appropriate treatment and safeguarding lung function.